Simulation of reactive distillation column for 2-ethyl hexyl acrylate production from dilute acrylic acid - Tay, Hong Luan (2014)
Acrylic acid (AA) is an unsaturated organic acid, very toxic and hazardous to the environment. Unfortunately, dilute acrylic acid (AA) has commonly produced as a by- product in many chemical and petrochemical processes such as manufacturing of acrylic esters. The recovery of dilute AA from the wastewater streams has become a growing concern among researchers due to its economic and environmental issues. There are several conventional separation techniques such as adsorption, distillation and extraction were developed to treat the wastewater from the industries; however, they have their own drawbacks respectively. One of the promising methods to purify the wastewater and economically sustainable is through esterification process of the recovery acrylic acid with alcohols via reactive distillation column. To date, study about esterification by using dilute AA has not been reported in literature. In this present work, a simulation study of esterification reaction of 2-ethylhexan-1-ol and dilute AA via reactive distillation system in the presence of ion exchange resin catalyst was performed using Aspen Plus RADFRAC incorporated with thermodynamic model of UNIFAC. The effect of different operating variables such as Acrylic Acid concentration, reflux ratio, bottom rate, catalyst weight and optimum column configuration were studied in this present work. The best operating conditions and column configuration were identified with maximum recovery of acrylic acid was 83% for the feed concentration of 10wt% AA, 0.1 reflux molar ratio, 0.13kg/h bottom rate and 1.5kg/m of catalyst weight. The best column configuration for the esterification system of acrylic acid and 2-ethylhexanol consisted of 4 reactive stages, 10 stripping stages and 4 rectifying stages, contributing to 18 numbers of stages with each stage of condenser and reboiler